Analysis of Human Resources Competence in the Digital Era As Staff Qualifications and Education in Quality Improvement at Kartika Husada Hospital in 2023 - Saputri, Agnes Ratna; Manik, Maggie Juntiven (Journal of Social Science and Business Studies, 2024)
The purpose of this study was to analyze the level of human resource (HR) competency in supporting hospital management information systems, and to understand the qualifications and impacts of the digital era on HR performance, including management strategies for facing structural transformation and work culture in the digital industry. This study employs a qualitative, descriptive exploratory approach to investigate the correlation between job satisfaction, hospital service quality, and HR competency. This method uses semi-structured interviews and open-ended questionnaires to collect data from human resources at the hospital, as well as from ten families of patients who have completed treatment. This study also collected secondary data through documents such as company profiles and websites. The researcher acted as a "key instrument" in the study, focusing on an in-depth understanding of service quality, job satisfaction, and HR competency in the context of the hospital. HR competency in the digital era affects job satisfaction and service quality, as evidenced by the expertise, nature, and motivation of good doctors and nurses, so that the quality of service provided to patients is better. The job satisfaction felt is caused by healing, compensation, and praise, so that doctors and nurses provide better service quality to patients. The results of the study indicate that the research model is acceptable. Competence of digital-era human resources, as demonstrated by education and competence, good and appropriate human resources, and better patient services, influences the quality of hospital services.